Secondary towns in West Africa and mobility challenges: Urban transport system in Ziniaré, Burkina Faso - (:unkn) unknown (My University, 2024)
Ziniaré, a medium-sized town in Burkina Faso, like many other towns in West Africa, is experiencing rapid and poorly controlled urban growth, both demographically and spatially, which is having a considerable impact on mobility needs. The aim of this book is to take stock of the urban transport system in this city. Using a methodological approach combining direct observation in the field, qualitative interviews and a quantitative study, the research highlights the existing transport resources and infrastructure in the municipality of Ziniaré, as well as the players involved in this system. The study also identifies the main challenges facing the town in terms of urban mobility and makes recommendations for sustainable improvements to transport in Ziniaré.
Keywords: African Research